IMPROVEMENT OF THE METHODS OF ROUTE SELECTION OF INNOVATIVE DEVELOPMENT OF AN ENTERPRISE ON THE BASIS OF THE ANALYSIS OF FINANCIAL AND STATISTICAL REPORTING - Irina A. Evseeva (Статистика и экономика, 2016)
An analysis of the indexes of the financial and innovation activity of industrial enterprises is given, six of them are identified. The methods of calculation of the indicators based on the financial and statistical reporting of enterprises is proposed. Practical testing of these methods is made by the example of Russian air entities. The appropriate recommendations for participation in the innovative activity are introduced.